The potential for using alcohol and tobacco taxes to fund prevention and control of noncommunicable diseases in Caribbean Community countries - Althea La Foucade; Charmaine Metivier; Samuel Gabriel; Ewan Scott; Karl Theodore; Christine Laptiste (Pan American Health Organization, 2018)
Objectives. To determine the extent to which increased taxes on alcohol and tobacco products in Caribbean Community (CARICOM) countries might successfully reduce consumption of those products and raise revenues, which could then be channeled into noncommunicable disease (NCD) prevention and control initiatives. Methods. The Tobacco Tax Simulation (TaXSiM) model, which was developed by the World Health Organization (WHO), was used to simulate the impact of tax changes on alcohol and tobacco products in three CARICOM member countries. Estimates of the NCD response cost in the 15 countries that are full members of CARICOM were also produced. Results. For the 15 full-member CARICOM countries, the revenues from increased excise taxes on beer, rum, and cigarettes associated with a 5.0% reduction in consumption were estimated at US$ 86.32 million. This expected revenue intake from excise taxes exceeded the estimated US$ 52.73 million required to respond to NCDs in those 15 CARICOM countries. The amount also exceeds US$ 78.87 million, which will be required if there is a 50.0% increase in the per capita NCD response cost. Conclusions. The findings showed that for CARICOM countries, there is a substantial potential for revenue generation from increases in taxes on alcohol and tobacco, as well as for decreases in consumption of the products. Although increased taxes on alcohol and cigarettes can sufficiently cover the cost of controlling NCDs among CARICOM countries, a comprehensive response also requires widespread participation from various sectors.